Multiple sclerosis: experimental models and reality - Lassmann, Hans (Acta Neuropathol, 2016)
One of the most frequent statements, provided in different variations in the introduction of experimental studies on multiple sclerosis (MS), is that “Multiple sclerosis is a demyelinating autoimmune disease and experimental autoimmune encephalomyelitis (EAE) is a suitable model to study its pathogenesis”. However, so far, no single experimental model covers the entire spectrum of the clinical, pathological, or immunological features of the disease. Many different models are available, which proved to be highly useful for studying different aspects of inflammation, demyelination, remyelination, and neurodegeneration in the central nervous system. However, the relevance of results from such models for MS pathogenesis has to be critically validated. Current EAE models are mainly based on inflammation, induced by auto-reactive CD4(+) T-cells, and these models reflect important aspects of MS. However, pathological data and results from clinical trials in MS indicate that CD8(+) T-cells and B-lymphocytes may play an important role in propagating inflammation and tissue damage in established MS. Viral models may reflect key features of MS-like inflammatory demyelination, but are difficult to use due to their very complex pathogenesis, involving direct virus-induced and immune-mediated mechanisms. Furthermore, evidence for a role of viruses in MS pathogenesis is indirect and limited, and an MS-specific virus infection has not been identified so far. Toxic models are highly useful to unravel mechanisms of de- and remyelination, but do not reflect other important aspects of MS pathology and pathogenesis. For all these reasons, it is important to select the right experimental model to answer specific questions in MS research.